THE FORMATION OF THE ENVIRONMENTAL AGENDA OF THE UNITED NATIONS GENERAL ASSEMBLY (1946-2016) - E. A. Bliznetskaya; E. P. Vasilenko (Vestnik MGIMO-Universiteta)
The history of an environment as an issue of the international politics pays remarkably little attention to the circumstances in which the environmental agenda develops and to its constitutive issues. The Stockholm Conference on the human environment is one of the important milestones that made the environment as an issue of international concern. However, its success would be impossible without the immense experience in addressing environmental issues gathered at the multilateral level. A review of the literature on the research topic shows that the term «environmental agenda» is not always used properly, there is a lack of empirical data to explain the «greening» of international relations. Indeed, given the fragmented nature of international environmental governance, specifically within the framework of the United Nations, it is difficult to trace the evolution of the environmental agenda from the first days of Organization to the present. For identification and definition of the content of the environmental agenda, the authors used the content analysis of the title of the resolutions of the UN General Assembly adopted in the period from 1946 to 2016. The research identified environmental issues of high priority: sovereignty over resources, environment, sustainable development, desertification, climate, natural disasters. The analysis made it possible to track their appearance on the agenda in chronological order. Also, we identified the issues underlying the formation of the environmental agenda of the General Assembly, namely international security issues related to nuclear weapons and economic development. In addition, we examined some voting patterns on environmental issues, the dynamics of changes in the attention of UN member states to key issues such as sustainable development, desertification, climate, sovereignty over natural resources.